2020
DOI: 10.13057/biodiv/d210920
|View full text |Cite
|
Sign up to set email alerts
|

Induction of autotetraploid Moringa plant (Moringa oleifera) using oryzalin

Abstract: Abstract. Ridwan, Witjaksono. 2020. Induction of autotetraploid Moringa plant (Moringa oleifera) using oryzalin. Biodiversitas 21: 4086-4093. Moringa (Moringa oleifera Lam.) is a plant with high nutritional content and has been widely used as a vegetable and health food ingredient, but its utilization and productivity have not been optimal. Increasing plant productivity can be done by increasing biomass which can be obtained through increasing plant ploidy. This study aims at obtaining tetraploid Moringa by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
6
0
2
Order By: Relevance
“…The plant height, number of leaves, and size of the leaf of tetraploid taro plants also displayed smaller than the diploid ones. In several species of plants, it is known that tetraploid plants generally have larger plant sizes (plant height, leaves, and flowers), such as, moringa (Ridwan and Witjaksono, 2020), hydrangea (Deans et al, 2021), caladium (Zhang et al, 2020), and ginger (Zhou et al, 2020). However, in some species of plants, tetraploid plants have smaller leaf sizes, such as, watermelon plants (Bae et al, 2020), slower growth in eucalyptus plants (Fernando et al, 2019), and lower fresh and dry weight in rubber dandelion plants (Taraxacum kok-saghyz) (Luo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plant height, number of leaves, and size of the leaf of tetraploid taro plants also displayed smaller than the diploid ones. In several species of plants, it is known that tetraploid plants generally have larger plant sizes (plant height, leaves, and flowers), such as, moringa (Ridwan and Witjaksono, 2020), hydrangea (Deans et al, 2021), caladium (Zhang et al, 2020), and ginger (Zhou et al, 2020). However, in some species of plants, tetraploid plants have smaller leaf sizes, such as, watermelon plants (Bae et al, 2020), slower growth in eucalyptus plants (Fernando et al, 2019), and lower fresh and dry weight in rubber dandelion plants (Taraxacum kok-saghyz) (Luo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Reports of increased protein content in tetraploid plants also showed in ginger (Zingiber officinale Roscoe cv. 'Fengtou') (Zhou et al, 2020) and in moringa plants (Ridwan and Witjaksono, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Masyarakat Bangka Belitung mengenal umbi kemili dengan sebutan tanaman kemili. Tanaman umbi kemili merupakan salah satu sumber komoditas pangan pertanian yang tumbuh subur di negara yang beriklim tropis dan sub tropis, tetapi tanaman ini belum banyak diketahui oleh masyarakat indonesia, hanya sebagian penduduk di pulau Jawa, Bali, Sumatera dan Madura (Ridwan et al, 2016). Tanaman kemili ini masih belum populer di kalangan masyarakat Bangka Belitung sehingga kandungan di dalam umbi kemili belum termanfaatkan oleh masyarakat untuk kebutuhannya.…”
Section: Pendahuluanunclassified
“…Asante et al (2014) reported that the calcium content of drumstick leaf in Ghana is ranging from 1474 mg kg -1 to 1880 mg kg -1 . Ridwan and Witjaksono (2020) reported higher calcium content of drumstick leaf from Indonesia which reached 1776-2414 mg kg -1 . Several other reports regarding the high nutritional content of drumstick trees have also been published by Moyo et al (2011), Melo et al (2013), Isitua et al (2015), and Brilhante et al (2017).…”
Section: Introductionmentioning
confidence: 97%